Catalytically active membrane-like devices: ionic liquid-hybrid organosilicas decorated with palladium nanoparticles - Luza, Leandro; Rambor, Camila P.; Gual, Aitor; Bernardi, Fabiano; Domingos, Josiel B.; Thomas, Grehl; Bruner, Philipp; Dupont, Jairton (American Chemical Society, 2016)
Ionic liquid (IL)-hybrid organosilicas based on 1-n-butyl-3-(3-trimethoxysilylpropyl)-imidazolium cations associated with hydrophilic and hydrophobic anions decorated with well dispersed and similar sized (1.8–2.1 nm) Pd nanoparticles (Pd-NPs) are amongst the most active and selective catalysts for the partial hydrogenation of conjugated dienes to monoenes. The location of the sputter-imprinted Pd-NPs on different supports, as determined by RBS and HS-LEIS analysis, is modulated by the strength of the contact ion pair formed between the imidazolium cation and the anion, rather than the IL-hybrid organosilica pore size and surface area. In contrast, the pore diameter and surface area of the hybrid supports display a direct correlation with the anion hydrophobicity. XPS analysis showed that the Pd(0) surface component decreases with increasing ionic bond strength between the imidazolium cation and the anions (contact ion pair). The finding is corroborated by changes in the coordination number associated with the Pd-Pd scattering in EXAFS measurements. Hence, the interaction of the IL with the metal surface is found to occur via IL contact pairs (or aggregates). The observed selectivities of ≥99% to monoenes at full diene conversion indicate that the selectivity is intrinsic to the electron deficient Pd-metallic surfaces in this “restricted” ionic environment. This suggests that IL-hybrid organosilica/Pd-NPs under multiphase conditions (“dynamic asymmetric mixture”) operate akin to catalytically active membranes, i.e. far from the thermodynamic equilibrium. Detailed kinetic investigations show that the reaction rate is zero-order with respect to hydrogen and dependent on the fraction of catalyst surfaces covered by either the substrate and/or the product. The reaction proceeds via rapid inclusion and sorption of the diene to the IL/Pd metal surface saturated with H species. This is followed by reversible hydride migration to generate a π-allyl intermediate. The reductive elimination of this intermediate, the formal rate-determining step (RDS), generates the alkene that is rapidly expelled from the IL phase to the organic phase.